Risk Prediction Model for Uncontrolled Hypertension in Chinese Community - Gao, Zhiping; Chen, Shiqun; Huang, Xiaoyu; Ye, Jianfeng; Liu, Jin; Huang, Zhidong; Chen, Jiyan; Li, Liwen; Liu, Yong; Lin, Shuguang (Frontiers in Cardiovascular Medicine, 2022)
Background: Uncontrolled hypertension rate was still high across the China. The aim of this study was to develop and validate an index to help quantify the combination of sociobehavioral aspects to screen high risk patients in uncontrolled hypertension in Chinese primary care. Methods: A cross sectional study, included 1039 of patients with hypertension in Chinese community. We assessed independent risk factors of uncontrolled blood pressure (defined as having a blood pressure ≥140/90mmHg, even with anti-hypertensive therapy) and develop risk prediction model. Results: Among the 1039 patients (males were 549, average age was 61±13 years), 452 (43.5%) were uncontrolled hypertensive. Multivariable analysis showed that worker, no health insurance, non-marital status and other sociobehavioral aspects were independent risk factors of uncontrolled hypertension, which were included the final prediction model. With internal validation by bootstrap method, the risk score showed good discriminating ability and predicting ability for the incidence of uncontrolled hypertension (C-static: 0.771). Conclusions: Our study showed that nearly half of the patients suffered uncontrolled hypertension in the Chinese community and established prediction model with good predictability to help quantify the combination of sociobehavioral aspects to screen high risk patients in uncontrolled hypertension.